Aloe Vera Gel Compression as Breast Engorgement Pain Relief - Lady Wizia; Evi Susanti (Women, Midwives and Midwifery, 2021)
Background: Breast engorgement is a condition where the breast becomes firm, diffuse, painful overfilling due to infrequent or ineffective removal of milk from the breasts. Engorgement usually begins around days 3 to 7 during the postpartum period when the breast milk starts to come out. Breast engorgement tends to experience by Primiparous patients. Purpose: This study aimed to determine the effects of Aloe vera gel compression on reducing breast engorgement pain on breastfeeding mother Methods: This was an experimental study with one group pretest-posttest. The analysis was performed in a Private midwifery Practice in Sarolangun. The sample of this study was twelve postpartum women who experienced breast engorgement. The intervention of this study was using aloe vera gel, as external usage with 10 mg for every square centimeter. The pain scale was measured twice, before and after the intervention. Pain scale measurement was using NRS ( Numeric Rating Scale) Results: paired T-test results p-value of 0.002 < 0.05 indicates that aloe vera compression brings positive impact on reducing breast engorgement pain scale in postpartum women Conclusion: Aloe vera compression can relieve pain associated with breast engorgement. Therefore, this intervention may be suggested to postnatal mothers for managing breast engorgement.